2023
DOI: 10.1002/advs.202303650
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Microenvironment‐Specific Bioinspired and Exosome‐Reinforced Hydrogel Scaffolds for Efficient Cartilage and Subchondral Bone Regeneration

Abstract: In clinical practice, repairing osteochondral defects presents a challenge due to the varying biological properties of articular cartilages and subchondral bones. Thus, elucidating how spatial microenvironment‐specific biomimetic scaffolds can be used to simultaneously regenerate osteochondral tissue is an important research topic. Herein, a novel bioinspired double‐network hydrogel scaffold produced via 3D printing with tissue‐specific decellularized extracellular matrix (dECM) and human adipose mesenchymal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…3D printing technology is an emergent and promising technique to fabricate microporous biomaterial scaffolds with customized structures and mechanical properties. , Researchers summarized the integration of various stem cell-derived EVs into biomaterial scaffolds for bone regeneration to achieve sustained release of bioactive molecules . A 3D printing hydrogel scaffold constructed with a decellularized extracellular matrix (dECM) and human adipose mesenchymal stem cell (MSC)-derived exosomes was proven to enhance regeneration of cartilage and subchondral bone tissues in a rat preclinical model . EVs as natural nanocarriers can transmit diverse substances such as DNA, RNA, and proteins, and further efficiently regulate the behavior of recipient cells .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D printing technology is an emergent and promising technique to fabricate microporous biomaterial scaffolds with customized structures and mechanical properties. , Researchers summarized the integration of various stem cell-derived EVs into biomaterial scaffolds for bone regeneration to achieve sustained release of bioactive molecules . A 3D printing hydrogel scaffold constructed with a decellularized extracellular matrix (dECM) and human adipose mesenchymal stem cell (MSC)-derived exosomes was proven to enhance regeneration of cartilage and subchondral bone tissues in a rat preclinical model . EVs as natural nanocarriers can transmit diverse substances such as DNA, RNA, and proteins, and further efficiently regulate the behavior of recipient cells .…”
Section: Resultsmentioning
confidence: 99%
“…66 A 3D printing hydrogel scaffold constructed with a decellularized extracellular matrix (dECM) and human adipose mesenchymal stem cell (MSC)-derived exosomes was proven to enhance regeneration of cartilage and subchondral bone tissues in a rat preclinical model. 67 EVs as natural nanocarriers can transmit diverse substances such as DNA, RNA, and proteins, and further efficiently regulate the behavior of recipient cells. 68 The main finding of this paper provides evidence that bioactive extracellular vesicles associated with different scaffold types highlight the potential benefits of regenerative medicine.…”
Section: Biocompatibility Assays and Cellmentioning
confidence: 99%
“…18). 166 The obtained hydrogel scaffold was able to mimic the spatial structure of natural bone, thus enabling the continuous release of exosomes. The combination of the two was able to provide a biomimetic microenvironment and corresponding stimuli for osteoblast adhesion and propagation, thereby accelerating cartilage regeneration.…”
Section: Classification Of Hydrogels For Bone Healingmentioning
confidence: 99%
“…15−17 Numerous researches have demonstrated that MSCs-derived exosomes (MSCs-Exos) exhibit beneficial bone regeneration effects through transporting intercellular biochemicals, and orchestrating multiple biological processes, and could avoid the risks of immune rejection and tumorigenicity from direct MSC transplantation, thus providing promising perspectives for cellfree therapy in regenerative medicine. 18,19 Furthermore, significant recent work revealed that MSCs are "environmental responsive" cells, with the bioactive components in their exosomes tunable with histological origin, physicochemical stimulation, and genetic modification. 20,21 This suggested that manipulation of exosomes to transfer desired cargoes has important implications in improving their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have consistently been a crucial reservoir of progenitor cells in tissue engineering, and hold great therapeutic promise in preclinical and clinical studies. Accumulating evidence have suggested that other than directly differentiate into effector cells to replace the tissue, MSCs exhibit a high paracrine activity via exosome release mechanism to regulate the surrounding microenvironment. , Exosomes are a type of nanosized membranous vesicles actively secreted by various cells, and are considered effective paracrine signal mediators by delivering bioactive molecules (including nucleic acids, proteins, and liquids) for intercellular communication and signal transduction. Numerous researches have demonstrated that MSCs-derived exosomes (MSCs-Exos) exhibit beneficial bone regeneration effects through transporting intercellular biochemicals, and orchestrating multiple biological processes, and could avoid the risks of immune rejection and tumorigenicity from direct MSC transplantation, thus providing promising perspectives for cell-free therapy in regenerative medicine. , Furthermore, significant recent work revealed that MSCs are “environmental responsive” cells, with the bioactive components in their exosomes tunable with histological origin, physicochemical stimulation, and genetic modification. , This suggested that manipulation of exosomes to transfer desired cargoes has important implications in improving their therapeutic potential. However, how to engineer MSCs-Exos with effective neuro- and osteo-promotive effects, and further to promote innervated bone regeneration, remains elusive.…”
Section: Introductionmentioning
confidence: 99%